Dampak Belanja Daerah Terhadap Pertumbuhan Ekonomi: Pendekatan Persamaan Simultan - Imamah, Nurul (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2018)
This study aims to find solutions to the problems of increasing economic growth and regional spending by research models involving regional expenditure variables and economic growth. This research also attempts to fill the gap in the need for regional expenditure development as regional spending can affect economic growth. This research was conducted by building an econometric model in a simultaneous equation system using panel data and estimated using the Two Stage Least Squares method (2SLS). The results of the analysis show that. Regional expenditure has a positive and significant effect on regional economic growth. This is in accordance with Hartati's recommendations, (2012); Marta Pascual and Santiago £ lvarez-GarcÌa (2006); Jamzani Sodik (2007); Wibisana (2014); (Amelia, 2013); (Adrian, 2013); but contrary to the findings of Agus Bagiyanto, (2015); Febian, (2014), as well as the factors that affect regional income and regional spending in each region are relatively the same